ANALISIS USAHA AGROINDUSTRI KERUPUK KULIT SAPI DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - wahyudi, Dedi '; Sayamar, Eri '; ', Eliza ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to know how the income of Agro Industry Cracker cow skin, and how much owest efficiency and added value of Agro Industry cracker cow skin. This research done on the efforts of Agro Industry cracker cow skin Kito Mamak City of Pekanbaru. This research conducted in March until 2016. The research carried out using the methods of the case study, research results can be summarized as follows: (1) The Total costs incurred by Cracker entrepreneurs cow skin Rp 108.702.944,00 per month. The acceptance of that obtained Rp 159.802.500,00 entrepreneurs per month. The Benefits of Rp 51.099.556,00 entrepreneurs per month, (2) Efficient business with the value of the R/C ratio of more than one of 1.47 means that every Rp1,00 costs incurred in the business of agro industry keruput cow skin gives the acceptance of 1.47 times from the costs. BEP analysis good entrepreneurs, at the time of producing entrepreneurs know of 98.20 and at the cost of Rp11.047.400,72. (3) added value of Rp 16.587,39 per kg, while the ratio of the value add cracker eating the skin of cattle is 40.21 yesterday percent.   Key Words: analysis, and agro-industry cracker cow skin.